2017
DOI: 10.1017/s0022029917000115
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic supplementation effects on milk fatty acid profile in ewes

Abstract: We hypothesised that probiotic feeding would alter the fatty acid (FA) profile of sheep's milk. Sixteen lactating ewes, kept under the same feeding and management practices, were randomly allocated to receive either a control diet or the same diet supplemented with a commercial multi-strain bacterial probiotic. Milk fat FA contents were monitored fortnightly for eight consecutive weeks from 14 d after lambing. Probiotic supplementation increased the contents of butyric and caproic acids in milk fat and had no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
1
5
0
1
Order By: Relevance
“…The FA concentrations of the milk analysed herein are similar to those reported by Payandeh et al (2017), who found the SFAs palmitic (16:0), stearic (18:0), myristic (14:0), capric (10:0), and butyric (4:0) acids at concentrations of 23.437, 11.847, 8.540, 5.880, and 3.667 g/100 g of fat, respectively. They also found oleic acid (18:1 n-9) to be the most abundant MUFA (23.232 g/100 g).…”
Section: Characterisation Of Milksupporting
confidence: 89%
“…The FA concentrations of the milk analysed herein are similar to those reported by Payandeh et al (2017), who found the SFAs palmitic (16:0), stearic (18:0), myristic (14:0), capric (10:0), and butyric (4:0) acids at concentrations of 23.437, 11.847, 8.540, 5.880, and 3.667 g/100 g of fat, respectively. They also found oleic acid (18:1 n-9) to be the most abundant MUFA (23.232 g/100 g).…”
Section: Characterisation Of Milksupporting
confidence: 89%
“…Greater milk 18:2n-6 and 18:3n-3 proportions were also found in the two latter studies. Conversely, a multi-strain product containing Lactobacillus acidophilus, Lactobacillus casei, Bifidobacterium thermophilum and E. faecium slightly decreased t11-18:1, c9t11-CLA and 18:2n-6 in ovine milk (Payandeh et al, 2017), and available data in lactating cows and beef (using mostly Propionibacterium spp. and Saccharomyces cerevisiae) do not seem very positive ( Supplementary Table S7).…”
Section: Plant Secondary Compoundsmentioning
confidence: 89%
“…The present study is part of a trial conducted to investigate the use of probiotics in lactating Sanjabi ewes. In a previous article, we reported the effects of probiotics on milk fatty acid composition (Payandeh et al 2017). In the current article, we focused on the effects of probiotics on productive results and blood biochemical indicators in an attempt to add information to the little published research on the matter.…”
Section: Discussionmentioning
confidence: 99%
“…Milk of Sanjabi ewes, besides used for lamb rearing, is consumed fresh or as cheese, yoghurt and other dairy products by the nomadic shepherds. Payandeh et al (2017) reported the effects of bacterial probiotics on milk fatty acid composition of Sanjabi ewes during lactation. The aim of the present work was to report the effects observed in the same experiment on milk yield, milk composition and blood plasma metabolite profile and enzyme activities.…”
Section: Introductionmentioning
confidence: 99%